NMDA receptor and APOE in Alzheimer’s disease: searching for connections - Escamilla, Sergio (Alzheimer's & dementia, 2023)
Background NMDA receptor (NMDAR) malfunctioning has been claimed as a crucial event in Alzheimer’s disease (AD), the most common form of dementia. While synaptic NMDAR activation leads to synaptic plasticity, extrasynaptic NMDAR activation leads to excitotoxicity, mitotoxicity and cell death. In the late onset form of AD, the APOE4 allele is the main genetic risk factor. Our aim is to study the influence of apoE4 on NMDAR function. Method We isolated synaptic and extrasynaptic membranes from APOE genotyped frontal cortex samples, from AD and non‐demented subjects. We studied the levels of NMDAR subunits GluN2B and GluN2A. We also evaluated the GluN2B phosphorylation at sites Y1472 and Y1336, associated to synaptic and extrasynaptic membrane location, respectively. We are also developing hiPSC‐derived cortical neurons from APOE genotyped AD and non‐AD subjects. Result At synaptic membranes, we found lower levels of GluN2B, Glun2A and pY1472‐GluN2B in AD respect to non‐demented patients. Inside the AD group, APOE4‐frontal cortex showed lower levels of GluN2B respect to non‐APOE4. At extrasynaptic membranes, no changes in GluN2B and Glun2A levels were observed, but phosphorylation at Y1336‐GluN2B was higher in AD respect to that in control. These results suggest that in AD, NMDAR are more likely to be found at the extrasynaptic membranes, where specific phosphorylation retain these subunits to those membranes. The lowest levels of NMDAR at the AD synapsis were found in APOE4 subjects. Conclusion We found that the APOE4 allele seems to compromise NMDAR levels and phosphorylation in a different manner in synaptic vs extrasynaptic membranes in the AD patients. We try to understand the mechanisms that govern these status using iPSC‐derived neurons. Understansing the relation between the NMDAR and apoE in AD could lead to new therapteutical approaches.